Reuse of Spent Coffee Grounds: Alternative Applications, Challenges, and Prospects—A Review - Wiktoria Sidło; Jolanta Latosińska (Applied Sciences)
Spent coffee grounds (SCGs) are a waste product generated after brewing coffee. For every ton of brewed coffee, approximately 650 kg of grounds are produced. Their disposal can have harmful environmental effects, making it necessary to find alternative uses for SCGs. The valorization of coffee’s bioactive compounds significantly contributes to environmental protection and management. According to the literature, SCGs can be utilized as fertilizers, sorbents, additives for biodiesel production, in bioelectricity, or as an enhancer for the calorific value of biomass. SCGs can also be used as substrates for producing various items, such as cups or plant pots, in the food, cosmetics, and construction industries. The applications of SCGs described in this review article were conducted under laboratory conditions. The aim of this article is to analyze the alternative uses of SCGs in various fields, highlighting the diversity of applications as well as key drawbacks and limitations associated with their use. Additionally, potential future research directions are outlined, which could contribute to a more efficient and sustainable utilization of SCGs.